A Pengaruh Penggunaan Limbah Styrofoam Terhadap Kuat Tekan Beton: Pengaruh Penggunaan Limbah Styrofoam Terhadap Kuat Tekan Beton - Demanda Prajika; Selpi, Selpi Herlina; Bastoni Hassasi; Lina Flaviana Tilik; Tri Kurnia Rahayu.J (Politeknik Negeri Sriwijaya, 2025)
Concrete is a structural material that is commonly used in the construction of buildings, roads, bridges and others. Concrete has a weakness, namely its specific gravity is high enough so that the dead load on a structure becomes large and the tensile strength is weak. The purpose of this study was to determine the effect of using Styrofoam waste on the compressive strength of concrete. This study uses Styrofoam waste as a partial substitution of the volume of coarse aggregate and fine aggregate with variations of 0% 5%, 10%, 15%, 20%, 25%, 30%, and 35% by using K-300 concrete quality and concrete. cube-shaped test with a size of 15 cm x 15 cm x 15 cm totaled 48 test objects. The compressive strength test was carried out at the age of 14 and 28 days of treatment. From the test results, the compressive strength of normal concrete at the age of 28 days is 318.81 kg/cm3, while after using Styrofoam waste the compressive strength is 179.50 kg/cm3 (5% Styrofoam), 162.72 kg/cm3 (10% Styrofoam), 142.15 kg/cm3 (15% Styrofoam), 103.94 kg/cm3 (20% Styrofoam), 80.32 kg/cm3 (25% Styrofoam), 64.71kg/cm3 (30% Styrofoam), and 59.95 kg/cm3 (35% Styrofoam). Based on the test results show that the addition of Styrofoam waste causes the compressive strength of concrete to decrease as the percentage of Styrofoam waste increases.